2008
DOI: 10.1097/mnm.0b013e3282f4d307
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine transporter abnormalities in patients with essential tremor

Abstract: Our results show that some essential tremor patients may present mild abnormalities of striatal dopamine transporters and a typical Parkinson's disease-like pattern of uptake loss. These findings suggest a link between the two disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 24 publications
2
50
0
5
Order By: Relevance
“…Moreover, two studies reported a mild reduction in striatal dopamine transporter binding in 60 ‘pure’ essential tremor patients compared to 59 healthy controls although less severe compared to 80 Parkinson's disease patients (Gerasimou et al, 2012; Isaias et al, 2008). The reduced dopaminergic uptake pattern differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two studies reported a mild reduction in striatal dopamine transporter binding in 60 ‘pure’ essential tremor patients compared to 59 healthy controls although less severe compared to 80 Parkinson's disease patients (Gerasimou et al, 2012; Isaias et al, 2008). The reduced dopaminergic uptake pattern differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the standardized uptake value ratio (SUVR FDG ) was calculated for each subject as the ratio of mean count per voxel of basal ganglia VOIs to mean count per voxel of the global 18 F‐FDG brain uptake. Additionally, for 123 I‐FP‐CIT the asymmetry index (AI) and the putamen‐caudate ratio (PCIDX)18 were also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that patients with PD were more likely to have ET while patients with ET were four times more likely than controls to develop PD (Tan et al 2008;Benito-León et al 2009). Dopaminergic deficiency and brainstem Lewy bodies (LB) have been demonstrated in both ET and PD (Isaias et al 2008). Patients with familial-linked PD genes (such as LRRK2) can present with ET (Skipper et al 2005), and alpha synuclein promoter polymorphism has been associated with both ET and PD (Tan et al 2000).…”
Section: Introductionmentioning
confidence: 98%